Design and Development of an Interactive Web-Based Simulator for Trauma Training: A Pilot Study. - Larraga-García, Blanca; Castañeda López, Luis; Rubio Bolívar, Francisco Javier; Quintana-Díaz, Manuel; Gutiérrez, Álvaro (Journal of Medical Systems, 2021)
Trauma is the leading cause of death in people under 45 years old and one of the leading causes of death in the world. Therefore, specific trauma training during medical school as well as after it is crucial. Web-based learning is an important tool in education, offering the possibility to create realistic trauma scenarios. A web-based simulator has been developed and a pilot study has been accomplished to trial the simulator. A pelvic trauma scenario was created and 41 simulations were performed, 28 by medical students and 13 by doctors. The data analyzed are the actions taken to treat the trauma patient, the evolution of the vital signs of the patient, the timing spent on deciding which action to take, when each action was performed and the consequence that it had on the patient. Moreover, a post-simulation questionnaire was completed related to the usability of the simulator. The clinical treatment performance of doctors is better than the performance of medical students performing more actions correctly and in the right sequence as per ATLS recommendations. Moreover, significant differences are obtained in the time response provided to the patients which is key in trauma. With respect to the usability of the tool, responses provide a positive usability rating. In conclusion, this pilot study has demonstrated that the web-based training developed can be used to train and evaluate trauma management. Moreover, this research has highlighted a different approach to trauma treatment between medical students and doctors.